Implementation of Islamic Economic Values in Online Transactions - Kamiruddin Kamiruddin; Hardianti Hardianti; Ida Farida (Budapest International Research and Critics University, 2021)
This study examines the implementation of Islamic values in online transactions. This study aims to determine the readiness of the Raisa Collection in applying Islamic values, to determine the application of Islamic values in the Raisa Collection in online transactions, to determine the application of Islamic values in the Raisa Collection in online transactions to be used on an ongoing basis, and to determine constraints. - Constraints experienced by Raisa Collection in applying Islamic economic values in online transactions. The research method used is qualitative research using field research using data collection techniques that include observation, interviews, and documentation. The analysis technique used is descriptive analysis techniques. The results showed that: (1) Raisa Collection has tried to apply Islamic values since the beginning of its business, even though it has used bank funds. (2) In conducting its business, Raisa Collection always prioritizes customer satisfaction and continues to serve complaints from consumers. The author's implications for the Raisa Collection owner are; (1) Maintain the principles or values of Islamic economics implemented. (2) Adding sales products.